2013
DOI: 10.1038/cdd.2013.110
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of lncRNA GAS5 by miR-21

Abstract: In addition to protein-coding genes, the human genome makes a large amount of noncoding RNAs, including microRNAs and long noncoding RNAs (lncRNAs). Both microRNAs and lncRNAs have been shown to have a critical role in the regulation of cellular processes such as cell growth and apoptosis, as well as cancer progression and metastasis. Although it is well known that microRNAs can target a large number of protein-coding genes, little is known whether microRNAs can also target lncRNAs. In the present study, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
337
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(353 citation statements)
references
References 54 publications
14
337
2
Order By: Relevance
“…It has been reported that lncRNA GAS5 was negatively regulated by miR-21 in breast tumors, hepatocellular carcinoma and osteoarthritis. GAS5 was also capable of suppressing miR-21 through an lncRNA/miRNA interaction, implying a feedback loop between GAS5 and miR-21 (8,(25)(26)(27). However, in the present study, GAS5 as well as miR-21 were identified to be upregulated in the CD4 + T cells of SLE patients, which may be associated with different types of diseases and cells (8,28,29).…”
Section: Discussioncontrasting
confidence: 60%
“…It has been reported that lncRNA GAS5 was negatively regulated by miR-21 in breast tumors, hepatocellular carcinoma and osteoarthritis. GAS5 was also capable of suppressing miR-21 through an lncRNA/miRNA interaction, implying a feedback loop between GAS5 and miR-21 (8,(25)(26)(27). However, in the present study, GAS5 as well as miR-21 were identified to be upregulated in the CD4 + T cells of SLE patients, which may be associated with different types of diseases and cells (8,28,29).…”
Section: Discussioncontrasting
confidence: 60%
“…Websites reviewed in (Fritah, et al 2014 (Rehmsmeier, et al 2004) has been used to examine miRNA/lncRNA interaction (Zhou, et al 2017a) http://bibiserv.techfak.unibielefeld.de/rnahybrid/ Increased by androgens in prostate cancer cells (Salameh, et al 2015) Suppressed by ERβ PCa-specific urine biomarker (Laxman, et al 2008 Represses onco-miR-21 (Zhang, et al 2013) inhibited miR-103 in EC cells (Guo, et al 2015) inhibited activation of the AKT/mTOR pathway in PC3 PCa cells (Xue, et al 2016a) Low expression correlated with poor prognosis in thyroid cancer tissues, co-immunoprecipitates with PI3K in HEC-1B EC cells Downregulated in breast , prostate , endometrial Sun et al 2017a), and PTC (Murugan et al 2017) tumors…”
Section: Declaration Of Interest and Fundingmentioning
confidence: 99%
“…A total of 15 BALB/c (nu/nu) male mice (200±2.6 g; age, 3 months) from the Animal Center of Guangzhou Province (Guangdong, China) received subcutaneous injections of 2x10 6 HepG2 cells into the axillae bilaterally. The mice were housed in a pathogen-free environment at a temperature of 20-26˚C and were exposed to 12 h light/dark cycles with free access to food and water.…”
Section: Design and Construction Of A Eukaryotic Expression Vector Formentioning
confidence: 99%
“…Small ncRNAs, including the well-documented microRNAs (miRNAs or miRs), have received great attention, since they are important in cancer (5). It has been proposed that lncRNAs are involved in the epigenetic regulation of coding genes, and thus, exert a powerful effect on a number of physiological and pathological processes, including the pathogenesis of numerous human cancers (6). It has been reported that lncRNA HOX transcript antisense intergenic RNA (HOTAIR) expression is significantly higher in HCC tissues than in adjacent non-cancerous tissues (7).…”
Section: Introductionmentioning
confidence: 99%